Intangible investments and innovation propensity. Evidence from the Innobarometer 2013 - Sandro Montresor; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2014)
This paper investigates the innovation impact of intangibles by considering the decision of firms to invest in a comprehensive set of them. By using a new survey on a large sample of firms in 28 EU (plus 8 non-EU) countries, we first identify the principal components of the resources firms invest in six kinds of intangibles. Their contribution to the firms' propensity to introduce new products and/or processes is then estimated with a two-step model, which addresses the endogeneity of the focal regressors through theoretically consistent instruments. A firm's innovativeness depends on its choice of using internal vs. external resources for its intangible investments more than on their actual amount, and on the kind of assets these investments are directed to. Intangibles need to be managed strategically in order to have an innovation impact and the policy support of this type of investment must take this strategic use into account.
Keywords: O30; O32; O33; 330; Innovation; Intangibles; R&D